Feeding Time and Botanical Composition of Diets Selected by Indigenous Goats on Native Pastures in Malaysia - Paul Van, Mele; Anthonysamy, Samy; Symoens, Chantal; Beeckman, Hans (Universiti Putra Malaysia Press, 1994)
The feeding time, grazing behaviour and botanical composition of diets selected by the indigenous Kambing Kacang on different native pastures of Selangor State, West Malaysia, were determined by direct observation during Nov - Dec 1993. Four herds were selected according to their grazing area (abandoned ricejield, roadside verges, waste ground and orchard) and monitored. Grazing animals travelled from 0.6 to 5.6 km daily. Depending on the locality of the grazing area and the forage available, time spent feeding ranged from 79.2 to 152.7 min. The herds were observed to first select the most juvenile plant parts which Provided the highest quality of diet. In terms of time spent on each species, the main species selected in descending order of importance were: Mimosa pudica, Ottochloa nodosa, Asystasia intrusa, Mikania cordata, Paspalum conjugatum, Axonopus compressus and Ischaemum timorense. The vegetation composition of the four grazing areas was assessed by means of representative plots. Vegetation covered 100% of the total sample area except on the waste ground (51 %). From records offeed selection and vegetation available, Preference indices were calculated for groups and individual plant species. Herbs appeared to be very palatable, with Mimosa pudica among legumes by far the most palatable. Judging by the feeding tirne., it would app'ear that the goats could not adequately meet their dry matter demands. Supplementation strategies based on diet selectivity and available resources may have to be developed to increase their productivity.